Synchrotron‐Based Phase‐Contrast Micro‐CT Combined With Histology to Decipher Differences Between Hereditary and Sporadic Pediatric Pulmonary Veno‐Occlusive Disease - Ida Jeremiasen; Niccolò Peruzzi; Elna Lampei; Sofie Meyer; Levent M. Akyürek; Erik Gebre‐Medhin; Ceren Mutgan; Peter Dorfmüller; Lavinia Neubert; Danny Jonigk; Csaba Galambos; Karin Tran‐Lundmark (Pulmonary Circulation)
ABSTRACT Pulmonary veno‐occlusive disease (PVOD) is a lethal variant of pulmonary hypertension. The degree of pulmonary arterial involvement varies. Here, we compare two PVOD patients who were transplanted at 8 years of age, whereof one is a homozygous EIF2AK4 mutation carrier. Tissue was imaged with synchrotron‐based micro‐CT and the results were compared with clinical data and sectioned tissue was analyzed with histology, immunohistochemistry, immunofluorescence, and in situ hybridization. Chest CT of the noncarrier exhibited scattered poorly defined ground‐glass opacities and marked septal lines, whereas the mutation carrier showed numerous nodular centrilobular ground‐glass opacities and sparse septal lines. The noncarrier developed pulmonary edema with vasodilators and 3D imaging combined with histology showed severe obstruction of interlobular septal veins and medial hypertrophy of pulmonary arteries, but no arterial or arteriolar intimal fibrosis. In contrast, the mutation carrier exhibited only mild intimal fibrosis in interlobular septal veins but severe arterial and arteriolar remodeling, including intimal fibrosis, tortuous course of arterioles, muscularization extending to the alveolar duct level and multiple vascular lumens within the same pulmonary arterial adventitia. Both patients had focally thickened alveolar septa with areas of pulmonary capillary hemangiomatosis (PCH) which colocalized with increased capillary muscularization, tenascin C expression, and deposition, as well as with matrix metalloproteinase‐9 (MMP9)/CD45 positive cells. In conclusion, synchrotron‐based phase‐contrast micro‐CT is valuable for understanding vascular remodeling. Significant differences were observed between heritable and sporadic PVOD, which may influence management strategies.